2008
DOI: 10.1007/s00421-008-0751-5
|View full text |Cite
|
Sign up to set email alerts
|

Myosin heavy chain isoform distribution in single fibres of bodybuilders

Abstract: The purpose of this study was to investigate the long-term effects of high intensity resistance training on myosin heavy chain (MHC) isoform composition of single fibres. Muscle biopsies were obtained from the right vastus lateralis of eight bodybuilders (BB) and seven physical education students (PES). Histochemical analyses were used to determine the fibre type distribution and the fibre cross-sectional area. MHC isoform composition of single fibres was determined with protein electrophoresis. The percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
0
22
2
Order By: Relevance
“…MYH7 is a slow molecular ATPase involved in muscle contraction . Our proteomic data indicated that MYH7 protein expression was upregulated ∼19 fold in cardiac hypertrophy (Fig.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…MYH7 is a slow molecular ATPase involved in muscle contraction . Our proteomic data indicated that MYH7 protein expression was upregulated ∼19 fold in cardiac hypertrophy (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Our informatics analysis led to the prioritization of 52 hypertrophy-associated protein candidates down to four proteins, including ANXA2, IGFBP7, MYH7, and DESM. MYH7 is a slow molecular ATPase involved in muscle contraction [32]. Our proteomic data indicated that MYH7 protein expression was upregulated ∼19 fold in cardiac hypertrophy (Fig.…”
Section: Establishment Of Biomarkers Of Heart Failurementioning
confidence: 80%
“…Although hybrid fibers definitely play a role in muscle fiber type transitions, a number of studies have now shown that hybrid fibers also form a common component of normal muscles (1,16,25,60). Many of these hybrid fibers represent very stable phenotypes, even in the face of different types of exercise (25,28,40). The relative proportion of hybrid fibers varies among different muscles (1,16,25) and even among anatomical regions within the same muscle (16,25).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported the transition from fast-to-slow muscle fiber types and MHC isoforms after resistance training (Roy et al, 1997;Carroll et al, 1998;Sharman et al, 2001). Kesidis et al (2008) observed a high percentage of fibers expressing MHCIIa and MHCI/ IIa in bodybuilders, compared to non-trained individuals. Similarly, Otis et al (2007) in a study on tumorbearing rats submitted to functional overload, observed a reduction in MHCIIb isoform, associated with increased levels of MHCI isoform.…”
Section: Skeletal Muscle Changes During Resistance Trainingmentioning
confidence: 99%